Stochastic Computing Correlation Utilization in Convolutional Neural Network Basic Functions - Hamdan Abdellatef; Mohamed Khalil Hani; Nasir Shaikh Husin; Sayed Omid Ayat (Universitas Ahmad Dahlan, 2018)
In recent years, many applications have been implemented in embedded systems and mobile Internet of Things (IoT) devices that typically have constrained resources, smaller power budget, and exhibit